PROFIL PENGGUNAAN OBAT ANTIDIARE PADA BALITA DI PUSKESMAS LURAH CIREBON PERIODE BULAN JANUARI – DESEMBER 2019 - Kunaedi, Aan; Hidayati, Nur Rahmi; Hasanah, Amna Nur (P3M STIKes Bakti Tunas Husada, 2021)
The increase in the number of diarrhea patients every year at the Cirebon Lurah health center, of course, needs to be a special attention to this disease, where research is aimed at finding out the profile of the use of antidiarrhea drugs in toddlers in the Cirebon Lurah Health Center in the period January – December 2019. Using retrospective study design, using patient prescriptions to see the treatment patterns of toddler patients at Puskesmas Lurah Cirebon, patient characteristics were obtained, and the profile of antidiarrhea medication use during the period january to December 2019. From the results of the prescription study of the period obtained results and conclusions: The age that has the largest number of cases is the age of 0-12 months, which is as many as 74 cases (30.84%), The number of patients with diarrhea toddlers most gendered male 138 cases (57.5%), The most widely used types of antidiarrheal drugs are zinc 2,300 tablets, drug doses and rules of use of drugs in the treatment carried out to overcome diarrheal diseases in toddlers in puskesmas Lurah is in accordance with MTBS guidelines unless oralit is not in accordance with MTBS.